BOOK NOTICES / BOEKAANKONDIGINGS - Lategan, Bernard C. (Scriptura, 1986)
Anderson, Ray S 1982. On being human: essays in theological anthropology. Grand Rapids: Eerdmans.Boff, Leonardo 1986. Ecclesiogenesis: The base communities reinvent the church. (Translated by Robert R Barr), Collins. Lux Verbi.Hoekema, Anthony A 1986. Created in God’s image. Grand Rapids: Eerdmans.Jewett, Paul K 1985. Election and predestination. Grand Rapids: Eerdmans.Newbigin, Lesslie 1986. Foolishness to the Greeks: The Gospel and Western culture. Grand Rapids: Eerdmans.Van Till, Howard j 1986. The fourth day: What the Bible and the Heavens are telling us about the creation. Grand Rapids: Eerdmans.Erler, R J & Marquard, R (eds) 1986. A Karl Barth reader. Grand Rapids: Eerdmans.Marshall, Paul 1984. Thine is the Kingdom: A Biblical perspective on the nature of government and politics today. Grand Rapids: Eerdmans.Neuhaus, Richard john 1986. Dispensations: The future of South Africa as South Africans see it. Grand Rapids: Eerdmans.Kinghorn, J (red) 1986. Die NG Kerk en apartheid. Johannesburg: Macmillan.Barth, Karl 1986 [1976]. Witness to the Word: A commentary on John I. (Ed; W Fürst; Tr: G W Bromiley). Grand Rapids: Eerdmans.Brown, Colin 1985. That you may believe: Miracles and faith then and now. Grand Rapids: Eerdmans.Bruce, F F 1984. The Gospel of John. Reprint. Grand Rapids: Eerdmans.Anderson, Ray S & Guernsey, Dennis B 1985. On being family: A social theology of the family. Grand Rapids: Eerdmans.Firet, Jacob 1986. Dynamics in pastoring. Translated by John Vriend. Grand Rapids: Eerdmans.Coggins, Richard J & Re’emi, S Paul 1985. Israel among the nations: Nahum, Obadiah, Esther. (Series: International Theological Commentary) Grand Rapids: Eerdmans.The international standard Bible encyclopedia. 1986. (Eds: G W Bromiley, E F Harrison, R K Harrison, W S Lasor, L T Geraty and E W Smith, Jr.) 4 Volumes. Grand Rapids: Eerdmans.The world of the Bible. 1986. (Eds: A S van der Woude, M J Mulder, B J Oosterhoff, J Reiling, H N Ridderbos, W C van Unnik, Translated by Sierd Woudstra.) Grand Rapids: Eerdmans.Estep, William R 1986. Renaissance and Reformation. Grand Rapids: Eerdmans.Neuhaus, Richard john (ed) 1986. Unsecular America. (Essays by P Johnson, E C Ladd, G M Marsden & R J Neuhaus). (The encounter series.) Grand Rapids: Eerdmans.1986. Virtue - public and private. (Essays by J H Billington, G Meilaender, R E Rodes Jr, B Semmel.) (The encounter series.) Grand Rapids: Eerdmans.Vassady, Bèla 1985. Limping along … Confessions of a pilgrim theologian. Grand Rapids: Eerdmans.Barth, K 1986. Wolfgang Amadeus Mozart. Translated by Clarence K Pott. Grand Rapids: Eerdmans.Louw, Johannes P (ed), 1986. Sociolinguistics and communication. (UBS Monograph Series, No 1) Bible Society of South Africa.Lategan, B C 1986. Die brief aan die Galasiërs. Kaapstad: NG Kerk-Uitgewers.Loader, J A 1986. Ecclesiastes. A practical commentary. (Series: Text and Interpretation.) Grand Rapids: Eerdmans.Santmire, H Paul 1985. The travail of nature. The ambiguous sociological promise of Christian theology. Lux Verbi.Van Huyssteen, Wentzel 1986. Teologie as kritiese geloofsverantwoording. Teorievorming in die sistematiese teologie. Reeks: RGN-studies in Navorsingsmetodologie nr 2.